2023
DOI: 10.3390/jcm12134419
|View full text |Cite
|
Sign up to set email alerts
|

Intimal CD31-Positive Relative Surfaces Are Associated with Systemic Inflammatory Markers and Maturation of Arteriovenous Fistula in Dialysis Patients

Abstract: Background: Arteriovenous fistula dysfunction is a widely disputed subject in the scientific literature on end-stage kidney disease (ESKD). The main cause of mortality and morbidity in these patients is the non-maturation or dysfunction of the arteriovenous fistula. Despite the many complications, the native arteriovenous fistula remains the gold standard in the treatment of these patients requiring renal replacement. This study aims to discuss the predictive role of some systemic inflammatory biomarkers (NLR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Similarly, in our study, although we observed a lower prevalence of male patients among those who experienced AVF failure, there was no difference between male and female patients. These findings corroborate other recently published articles by Kaller et al [8,9] and Mures , an et al [10], where the authors observed no gender-related differences in AVF maturation rate [8,9] and mortality among ESKD patients [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, in our study, although we observed a lower prevalence of male patients among those who experienced AVF failure, there was no difference between male and female patients. These findings corroborate other recently published articles by Kaller et al [8,9] and Mures , an et al [10], where the authors observed no gender-related differences in AVF maturation rate [8,9] and mortality among ESKD patients [10].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that inflammatory biomarkers based on blood cell counts of neutrophils, monocytes, platelets, and lymphocytes can predict AVF dysfunction [8][9][10] and long-term mortality in dialysis patients [10,16,17]. When the venous wall is exposed to arterial pressure, it undergoes a histological remodeling process that results in the proliferation, differentiation, and migration of smooth muscle cells (SMC), generating long-term intimal hyperplasia (IH) [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low pressure in the venous system, immediately after performing AVF and exposing the venous wall to arterial pressure, the remodeling process is initiated through wall distension, endothelial injury, local ischemia, and cell apoptosis ( 37 39 ). Overtime, these will lead to generation of inflammatory process at the venous wall and NIH ( 38 , 40 ). New methods, such as external stenting, have been developed and proposed to reduce NIH and local inflammation ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 In addition, studies have shown that inflammation at vascular access is also one of the main causes of arterial intimal hyperplasia and early thrombosis of local vessels. 6 It has been suggested that the initiating factors of intimal hyperplasia are vascular wall injury, immune/inflammatory response, and hemodynamic factors. 7 Recent studies 8 have shown that the intimal hyperplasia at the stenosis of the vascular access is obvious.…”
Section: Introductionmentioning
confidence: 99%